2018
DOI: 10.5944/rppc.vol.23.num.2.2018.21823
|View full text |Cite
|
Sign up to set email alerts
|

Invarianza factorial y temporal del Cuestionario de Regulación Emocional (ERQ)

Abstract: The Emotional Regulation Questionnaire (ERQ; Gross y John, 2003) is widely used to assess individual differences in reappraisal and suppression strategies of emotion regulation. The present study tests the factorial and temporal invariance of a Spanish adaptation of the ERQ on two samples of 1.980 participants aged 18-67 years. Psychometric properties, reliability, and factorial and temporal validity of the ERQ were calculated. Results of the confirmatory factor analysis showed the expected two-factor structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
0
7
0
9
Order By: Relevance
“…Given the location in which the study was conducted, the survey was necessarily brief, and additional variables and data could not be collected. Both tools were selected for this research given their low quantity of items as well as their use in different studies in Latin America, having been identified with adequate psychometric properties in different samples (Gabardo-Martins et al 2017 ; Mosqueda Díaz et al 2015 ; Pineda et al 2018 ). The average duration for completing the questionnaire was about 15 to 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Given the location in which the study was conducted, the survey was necessarily brief, and additional variables and data could not be collected. Both tools were selected for this research given their low quantity of items as well as their use in different studies in Latin America, having been identified with adequate psychometric properties in different samples (Gabardo-Martins et al 2017 ; Mosqueda Díaz et al 2015 ; Pineda et al 2018 ). The average duration for completing the questionnaire was about 15 to 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, emotional regulation was measured using Emotion Regulation Questionnaire (ERQ) [41] adapted to Spanish adolescents by [42]. This mono-factorial scale comprises 10 items that express the degree of agreement or disagreement in reference to how the adolescent regulates its emotions in two main dimensions; cognitive reevaluation (six items) (e.g., "I control my emotions by changing the way I think about the situation I am in") and emotional suppression (four items) (e.g., "I keep my emotions to myself").…”
Section: Instrumentsmentioning
confidence: 99%
“…Existen diferencias individuales en la capacidad y forma de regular las emociones, siendo algunas más exitosas que otras (Pineda, Valiente, Chorot, Piqueras y Sandín, 2018). Las estrategias de regulación emocional que mayor apoyo empírico han recibido son la reevaluación cognitiva y la supresión expresiva (Navarro et al, 2018).…”
Section: Estrategias De Regulación Emocionalunclassified